THE RELATIONSHIP BETWEEN THE CHEMICAL PROPERTIES OF SOIL AND THE COMPOUNDS SQUALENE AND LINOLENIC ACID - Aditya Candra; Tahara Dilla, Santi; Ika Waraztuty; Andri; Muhammad Yani; Said Aandy Saida (PT. Radja Intercontinental Publishing, 2025)
This research aims to determine the concentrations of secondary metabolites in Carica papaya (papaya) leaves and their correlation with soil chemical properties in Aceh Besar. Purposive sampling was used to select papaya plant leaves from the Kajhu and Ie Seuum areas for this study. Soil samples were collected from where the papaya leaf samples were obtained. Utilization of the maceration technique for extracting papaya leaves and identifying secondary metabolite compounds via Gas Chromatography Mass Spectrophotometry (GCMS). The chromatogram results indicated that squalene and linolenic acid were the compounds with the highest percentages. At the same time, the soil samples were subsequently analyzed for N, P, K, C, pH, and temperature content. Subsequently, the acquired data were subjected to multiple regression analysis. The findings indicated that the squalene content was 3.2–3.35% in Kajhu and 10.4–10.5% in Ie Seum, whereas linolenic acid levels were 10.18–10.21% and 4.03–4.05%, respectively. The squalene content positively correlates with P, pH, and temperature, whereas linolenic acid correlates solely with the P elements. The chemical properties of the soil do not significantly influence the content of squalene and linolenic acid.